Pengaruh Konsumsi Tempe terhadap Kadar Gula darah pada Penderita Diabetes Melitus di Kelompok Senam Ibu-Ibu di Kelurahan Talang Banjar Jambi - Iin Indrawati; Maimaznah Maimaznah (Jurnal Akademika Baiturrahim Jambi, 2020)
DM management that is more effective and efficient requires prevention and control programs that are on target. There are several risk factors associated with the incidence of DM, one of which is a behavioral factor. The behavior or lifestyle in question is eating habits. The purpose of this study was to determine the effect of tempe consumption on blood sugar levels of DM sufferers in the exercise groups of women in the Talang Banjar Village, Jambi.The research method used was a quasi-experimental one group pre and post experience test. The population is group of gymnastics mothers of gymnastics mothers who suffer from diabetes mellitus, amounting to 6 people, using total sampling techniques, and analyzed using T Test.The analysis showed that there was no effect of tempe consumption with blood sugar levels with a p value (p value 0.201).Although the results of the study did not show any influence, it is likely that this was caused by several things such as the small number of samples, and it was not determined whether the N sample was a type 1 or type 2 diabetes sufferer. diabetes mellitus as a controller or helps control blood sugar levels in the body.